The Life Experiences of Non-Muslim Students at Muhammadiyah University: A Phenomenological Study on Inclusive Islamic Education - Yusuf, Muhammad; Pajarianto, Hadi; Halim, Ibrahim; Amriani; Zhang, Miao (LETIGES, 2025)
This study aims to explore the experiences of non-Muslim students at Muhammadiyah University of Palopo within the context of inclusive Islamic education and to develop a relevant and contextual conceptual model. A qualitative approach with a hermeneutic phenomenological design was employed to investigate students' subjective experiences through in-depth interviews, participatory observation, and document analysis. The main findings include the adaptation process of non-Muslim students, which begins with a